112 How Will the Purebred Association Adapt to a Changing Beef Industry?. (7th May 2021) - McCully, Mark
Abstract: The role of the breed association has historically been to keep a registry of a pure breed, aggregate the performance data surrounding that one breed, develop breeding and selection tools, and conduct breed promotion. Larger associations have been able to augment that with operating magazines and other media, running branded beef programs, feeder calf marketing programs, and genetic evaluation for other breeds. The relevance of breed associations is being and will continue to be challenged as genomics and large commercial databases develop and allow for breeding and selection tools to be developed independently by large breeders or private entities. Gene editing and other such technology will also challenge the traditional seedstock models and opens the door for proprietary genetic lines. Breed associations may need to modify their traditional policies to incorporate these innovations. Supply chains will continue to become far more sophisticated and will incorporate more genetic information to guide management decisions and potentially validate brand promises around sustainability. To stay relevant, breed associations of the future will need to do the following: Balance the needs of diverse membership (show, hobby, lifestyle, etc.) with commercial industry value and significance. Have access to large amounts of data and be leaders in adopting the most current technologies. Deliver tools for breeders that enhance the profitability of commercial producers – identify optimum production levels vs maximum outputs. Work collaboratively with multiple supply chains providing the needed genetic information. Be a significant educational resource to breeders and commercial producers. Be a leader in research on breed improvement and genetic advancement. Have value-added programs that create real and sustained pull-through demand for the end product.